Pemberdayaan Masyarakat Melalui Penyuluhan Perilaku Hidup Sehat Dan Bersih (Phbs) Pada Anak-Anak Untuk Meningkatkan Derajat Kesehatan di SD Swasta Bharlind Tahun 2023 - Sari Rahma Fitri; Emelia Apriani Tampubolon (Indonesian Journal Publisher, 2023)
Clean and Healthy Living Behavior (PHBS) is all health behaviors that are carried out on awareness. There are many PHBS, hundreds of them. For example about nutrition: eating a variety of foods, taking blood supplement tablets, consuming iodized salt, giving babies and toddlers vitamin capsules. Primary school-age children are also very vulnerable to health problems due to an unhealthy diet. Food sold at school or in the school environment does not all meet health and safety standards, and school children tend to prefer unhealthy foods either because of inadequate knowledge or because they are easily influenced by advertisements The subjects in the service activities are elementary school children at Bharlind Elementary School. The delivery of counseling material using the lecture method, the implementation of the service which is assisted by the teacher and followed by a question and answer session This community service activity aims to improve the level of health at Bharlind Private Elementary School in 2023